Signal detection for orthogonal space-time block coding over time-selective fading channels: The H/sub i/ systems - Zheng, F.-C.; Burr, A.G. (IEEE transactions on wireless communications, 2006)
One major assumption in all orthogonal space-time block coding (O-STBC) schemes is that the channel remains static over the length of the code word. However, time-selective fading channels do exist, and in such case conventional O-STBC detectors can suffer from a large error floor in the high signal-to-noise ratio (SNR) cases. As a sequel to the authors' previous papers on this subject, this paper aims to eliminate the error floor of the H/sub i/-coded O-STBC system (i = 3 and 4) by employing the techniques of: 1) zero forcing (ZF) and 2) parallel interference cancellation (PIC). It is. shown that for an H/sub i/-coded system the PIC is a much better choice than the ZF in terms of both performance and computational complexity. Compared with the, conventional H/sub i/ detector, the PIC detector incurs a moderately higher computational complexity, but this can well be justified by the enormous improvement.